(untitled) (AL JAMI: Jurnal Ilmiah Keagamaan, Pendidikan dan Dakwah, 2023)
This research aims to discuss the significant role of Islamic education in shaping noble character traits among Muslims. The study examines the essence of Islamic education as a transformative force in instilling values such as compassion, integrity, and empathy in individuals. It explores how Islamic teachings, ethics, and practices serve as guiding principles in forming the moral compass of Muslims, fostering a sense of responsibility towards society, and promoting ethical behavior in various aspects of life. The research methodology employed is library research, utilizing a type of library research based on the search for several articles, journals, and other scholarly works related to pre-defined keywords. Subsequently, the researcher gathers, analyzes, and selects all sources to draw conclusions. The significance of this research lies in its ability to summarize how Islamic education not only prepares individuals for the present life but also equips them with values that guide their journey in the afterlife. The research findings indicate that through a combination of traditional teachings and contemporary methodologies, Islamic education empowers individuals with the knowledge and skills necessary to navigate the complexities of the modern world while upholding the principles of truth and moral excellence